Influence of chronic alcoholism and estrogen deficiency on the immunohistochemical expression of regulatory proteins of the bone resorption process in the periodontium of Wistar rats - Marchini, Adriana Mathias Pereira de Silva [UNESP] (2018)
Objective: The aim of this study was to investigate possible changes in immunohistochemical expression of proteins regulating the bone resorption process in the periodontium of rats subjected to alcoholism and/or estrogen deficiency. The investigated proteins were receptor activator of nuclear factor-kappa β ligand (RANKL), a protein that stimulates bone resorption, and osteoprotegerin (OPG), a protein that inhibits bone resorption. At the molecular level, decreased OPG expression and/or increased RANKL expression are consistent with a greater predisposition to bone resorption. Design: Wistar female rats were divided into ovariectomized (ovx) and non-ovariectomized (sham) groups, and subdivided into ad libitum diet (free diet), alcoholic diet (20% solution), and isocaloric diet (diet with a similar amount of calories as compared with groups ingesting an alcoholic diet). The alveolar bone crest and adjacent tissues were evaluated by immunohistochemical analyses for detection of OPG and RANKL. Results: A significant decrease in OPG expression and a significant increase in RANKL expression were observed in ovariectomized animals which received alcohol as compared with non-ovariectomized animals which received isocaloric diet (experimental control). When estrogen deficiency was evaluated independently of the diet type, a significant decrease in OPG expression and a significant increase in RANKL expression were observed in ovariectomized animals as compared with non-ovariectomized animals. Conclusions: Estrogen deficiency associated with alcoholic diet, as well as estrogen deficiency (analyzed independently of diet type), decreased the immunostaining for OPG and increased the immunostaining for RANKL in the periodontium of rats.